Powering battery sustainability: a review of the recent progress and evolving challenges in recycling lithium-ion batteries - Zheng, Panni; Young, David; Yang, Tairan; Xiao, Yunhao; Li, Zheng (Frontiers in Sustainable Resource Management, 2023)
As the global consumption of lithium-ion batteries (LIBs) continues to accelerate, the need to advance LIB recycling technologies and create a more robust recycling infrastructure has become an important consideration to improve LIB sustainability and recover critical materials to reuse in new LIB production. Battery collection, sorting, diagnostics, and second-life usage all contribute to the LIB logistics network, and developments in each of these areas can improve the ultimate recycling and recovery rate. Recent progress in LIB recycling technology seeks to increase the amount of valuable metal compounds, electrode materials, and other LIB components that are recoverable and that can be redeployed in new LIB production or other markets. This review establishes an overview of these developments and discusses the strengths and weaknesses of each major recycling technology. Of particular note are the differences in recycling technology and infrastructure requirements created by various LIB markets, as well as the techno-economic considerations for different recycling methods based on the evolving LIB formats and component compositions.